Assessment of cardiac biomarkers (Troponin, B-type natriuretic peptide, and D-Dimer) in patients with non-valvular atrial fibrillation and stroke: Assessment of cardiac biomarkers - Paulin, Bilonda K.; Cedric, Kabulo K.; Tamomh, Abdelhakam G.; Hui, Yang Dong (International Journal of Health Sciences, 2019)
Objectives: Atrial fibrillation (AF) is the most common arrhythmia treated in clinical practice, and the association of this arrhythmia with stroke has long been recognized. The combination of associated factors to identify stroke risk is still unclear; therefore, we aimed to determine the association between additional risk factors for non-valvular AF (NVAF) and first onset stroke patients and investigate the predictive ability of additional risks factors such as cardiac biomarkers and AF status for odds of incident stroke. Materials and Methods: We included 455 patients suffered from NVAF divided into two distinct groups (case–control observational study). Those two groups were based on whether the patients were having a first onset stroke (stroke group) or not having a stroke (non-stroke group). We made the baseline characteristic of our sample group from the substantial evidence of risk factors, lifestyle, and type of AF; to controversial risk described in the new international guideline of AF. Results: Statistically revealed that heart failure, coronary disease, cigarette smoking, type of AF, warfarin treatment, high sensitive troponin, and B-type natriuretic peptide (BNP) are associated with stroke in NVAF patients (P < 0.05). Otherwise, age, sex, hypertension, kidney disease, diabetes, thyroid disease, alcohol intake, season, aspirin, and D-dimer medication were not associated with stroke (P > 0.05). Multivariate analysis of age, smokers, coronary heart disease, heart failure, high sensitive troponin level, BNP, permanent AF, and warfarin was associated (P < 0.05). The combination of biomarkers with the clinical features can be useful (CHA2DS2-VASc/BS) for the prediction of stroke than CHA2DS2-VASc alone (P < 0.05). Conclusion: Impact of all associated factors and biological markers as additional risk factors may carry a synergy in this life-threatening event. Additionally, may hold a clinical role which may help to redefine and predict stroke event better than the current CHA2DS2-VASc.